FINANCIAL THE EFFECT OF EMOTIONAL INTELLIGENCE ON JOB SATISFACTION WITH WORK-LIFE BALANCE AND BURNOUT AS MEDIATION - Nathaya, Azzahra Dynaeira; Hidayat, Nurdin; Dalimunthe, Sholatia (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
This study aims to determine the effect of Emotional Intelligence on Job Satisfaction with Work-Life Balance and Burnout as a mediation at State Vocational High Schools Teachers in DKI Jakarta. The research method used is a quantitative method. The population in this study was teachers of State Vocational High Schools in DKI Jakarta with a sample of 255 teachers. The model in this study uses a path analysis model. The analytical technique used in this study is a SEM (Structural Equation Modeling) model which is operated with the SmartPLS version 3.0 program for hypothesis testing.